Identification of RUNX1 and IFNGR2 as prognostic-related biomarkers correlated with immune infiltration and subtype differentiation of low-grade glioma - Xia Zhang; Hongyu Chu; Yuan Cheng; Jie Ren; Wei Wang; Xicheng Liu; Xiaodong Yan (Biomolecules & Biomedicine, 2023)
Immune cell infiltration occurs in the tumor microenvironment (TME) and influences cancer progression through interaction with tumor cells. Runt-related transcription factors (RUNXs), RUNX1-3, are the master regulators of development and differentiation and are all important to the development of immune cells. However, the role of RUNXs in the immune cells of TME remains unclear. In this study, we first used online related databases and related LGG data from TCGA and CGGA to conduct bioinformatics analysis, which confirmed that RUNXs were significantly and positively correlated with immune infiltration in multiple tumors, especially in low-grade glioma (LGG) and there was the highest correlation between RUNXs and the progress and prognosis of LGG. Furthermore, the functional enrichment analysis revealed that RUNXs might be involved in the inflammatory and immune responses of the biological processes, and RUNXs were tightly associated with the multiple immune checkpoint molecules. Subsequent results confirmed that RUNX1, as an independent prognostic factor for LGG, may target interferon-gamma receptor 2 (IFNGR2) to regulate glioma cell proliferation, invasion, and migration. Besides, we also found that the expression levels of RUNX1 and IFNGR2 were significantly reduced, and their correlation was enhanced in the IDH-mutant subtype. Patients with a high expression of RUNX1 and/or IFNGR2 (HH/H) in the IDH-mutant subtype showed poorer prognosis and significantly increased infiltration of M2 macrophages. This finding implied the possible key role of RUNX1 in the differentiation of IDH mutant subtypes as well as in the formation of tumor microenvironment (TME) infiltration signatures by monitoring IFNGR2.